2020
DOI: 10.1038/s41598-020-58131-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of GM-CSF blocking on the phenotype and function of human monocytes

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a multipotent cytokine that prompts the proliferation of bone marrow-derived macrophages and granulocytes. In addition to its effects as a growth factor, GM-CSF plays an important role in chronic inflammatory autoimmune diseases such as multiple sclerosis and rheumatoid arthritis. Reports have identified monocytes as the primary target of GM-CSF; however, its effect on monocyte activation has been under-estimated. Here, using flow cytometry and ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…This may represent an immediate response of the immune system to try and remove the virus. GM-CSF also induces an inflammatory profile in human monocytes; should it have a similar role in cats, this would decrease the required stimulus threshold for activation [35]. In concert, IL-6 and GM-CSF released from newly infected monocytes could increase the monocyte pool and thereby ensure that sufficient cells are available to maintain viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…This may represent an immediate response of the immune system to try and remove the virus. GM-CSF also induces an inflammatory profile in human monocytes; should it have a similar role in cats, this would decrease the required stimulus threshold for activation [35]. In concert, IL-6 and GM-CSF released from newly infected monocytes could increase the monocyte pool and thereby ensure that sufficient cells are available to maintain viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF is one of those promising factors, which is secreted by CAR T-cells following activation and activates myeloid cells but does not appear to contribute to CAR-T cell function (37,65,86). In vitro inactivation of GM-CSF in CAR-T cells reduced myeloid cell-derived inflammatory cytokines (37), and in some studies GM-CSF inhibition reduced expression of some CRS associated cytokines, such as IL-6, but not IL-1b (37,65,(86)(87)(88). However, in animal studies, GM-CSF neutralization did not completely prevent inflammatory toxicities (86).…”
Section: Current Strategies To Prevent Inflammatory Toxicities Duringmentioning
confidence: 99%
“…GM-CSF is also an immunomodulatory cytokine, which can promote the differentiation of monocyte/M1 type macrophages and DCs, enhance their activities and antigen presentation, and amplify the body's immune response ( 26 , 95 ). Previous studies showed that the expression level of DC gene signature in renal cell carcinoma and NSCLC tissues was positively correlated with OS ( 27 ).…”
Section: Biological Response Modifiers To Boost the Effect Of Combinamentioning
confidence: 99%